A multi-tier framework for securing e-transactions in e-government systems of Saudi Arabia. (31st May 2011) - Gamlo, Amina; Bamasak, Omaima
Countries across the globe are working towards e-government realisation. One of the issues arising with the efforts to this realisation is the assurance of secure transactions while withholding high privacy standards. Different systems require different levels of security according to the services they provide to their users. This paper presents a survey of security measures implemented in e-government projects both locally (in the Kingdom of Saudi Arabia) and internationally, beginning with more established e-government systems around the world. Security of these systems will then be evaluated accordingly to a defined list of security requirements fitting the needs of local e-government projects. This will be the basis for the design and implementation of an e-transaction multilevel security system for e-government systems and for its evaluation.